Metal organic framework derived porous carbon materials excel as an excellent platform for high-performance packaged supercapacitors. Issue 11 (16th March 2021) - Chu, Xianyu; Meng, Fanling; Deng, Ting; Zhang, Wei
Abstract : This review systematically sums up the design principles and strategies for MOF precursors and discusses the relationship between MOF precursors and the target porous carbon for the accurate architecture of high-performance supercapacitors. Abstract : Designing and synthesizing new materials with special physical and chemical properties are the key steps to assembling high performance supercapacitors. Metal organic framework (MOF) derived porous carbon materials have drawn great attention in supercapacitors because of their large specific surface area, high chemical/thermal stability and tunable pore structure. Thus, the recent development of porous carbon as an electrode material for supercapacitors is reviewed. The types, design and synthesis strategies of porous carbon are systematically summarized. This review will be divided into three main parts: (1) the design and synthesis of MOF precursors and templates for MOF-derived porous carbon materials; (2) the application of different types of MOF-derived carbon in supercapacitors; and (3) the design of typical structures of porous carbon composites for supercapacitors. Finally, the problems and challenges confronted when using porous carbon are assessed and elaborated, and some suggestions on future research directions are proposed.